2019
DOI: 10.1556/1886.2019.00010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a glyphosate-containing herbicide on Escherichia coli and Salmonella ser. Typhimurium in an in vitro rumen simulation system

Abstract: Glyphosate (N-(phosphonomethyl)glycine) is the most-used herbicide worldwide. Many studies in the past have shown that residues of the herbicide can be found in many cultivated plants, including those used as livestock feed. Sensitivity to glyphosate varies with bacteria, particularly those residing in the intestine, where microbiota is exposed to glyphosate residues. Therefore, less susceptible pathogenic isolates could have a distinct advantage compared to more sensitive commensal isolates, probably leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…When summarizing the results of the analyses of rumen microbial products, the composition of the ruminal microbiome, the associations of rumen microbial taxa with feed and microbial products and finally the detection of fecal pathogenic Clostridia it becomes obvious, that the principal diet composition unsurprisingly had a strong impact on the ruminal microbiome and its fermentation products, while glyphosate apparently had no relevant effects. This is in agreement with in vitro observations using mixed cultures of microorganisms from ruminal fluid showing that glyphosate had no adverse effects on simulated ruminal microbiomes 29 , 30 . The absence of long-term glyphosate effects in the gastrointestinal tract is not surprising, since excess of amino acids is available and synthesis of aromatic amino acids can possibly be bypassed through transport 19 .…”
Section: Discussionsupporting
confidence: 92%
“…When summarizing the results of the analyses of rumen microbial products, the composition of the ruminal microbiome, the associations of rumen microbial taxa with feed and microbial products and finally the detection of fecal pathogenic Clostridia it becomes obvious, that the principal diet composition unsurprisingly had a strong impact on the ruminal microbiome and its fermentation products, while glyphosate apparently had no relevant effects. This is in agreement with in vitro observations using mixed cultures of microorganisms from ruminal fluid showing that glyphosate had no adverse effects on simulated ruminal microbiomes 29 , 30 . The absence of long-term glyphosate effects in the gastrointestinal tract is not surprising, since excess of amino acids is available and synthesis of aromatic amino acids can possibly be bypassed through transport 19 .…”
Section: Discussionsupporting
confidence: 92%
“…The RUSITEC system, which was used here, is a more complex system, which is able to maintain the core bacterial community of the rumen over a longer time (Wetzels et al, 2018). Our results agree with previous RUSITEC studies, which observed only minor effects of glyphosate on the rumen bacterial population and no effects on the growth of pathogenic bacteria (Riede et al, 2016;Bote et al, 2019). In a recent in vivo study with dairy cattle, Billenkamp et al (2021) observed differences for only four taxa, which, however, appeared to be linked closer to experimental conditions than to glyphosate application.…”
Section: Discussionsupporting
confidence: 89%
“…High glyphosate levels (10 mg/l) did also not affect establishment of Escherichia coli or Salmonella Ser. Typhimurium in the RUSITEC system (Bote et al, 2019). Schnabel et al (2017) did not observe adverse effects of a glyphosate-contaminated diet (intake up to 84.5 mg/d) on performance or energy balance of dairy cows, neither did this affect leucocytes or erythrocytes (Schnabel et al, 2020) or the rumen microbiome (Billenkamp et al, 2021).…”
Section: Introductionmentioning
confidence: 87%
“…Pathogens tend to have superior stress responses due to their higher adaptiveness under stress conditions; for example, the transition from the environment into their host [ 46 , 47 ]. Thus, glyphosate as a stress factor may reduce bacterial susceptibility, either as a stress response or via mutations and change the bacterial response to antibiotics [ 12 , 49 , 50 , 51 , 52 , 53 ]. In turn, the heavy use of antibiotics and other chemicals may lead to bacterial co- and cross-resistance to glyphosate and other antimicrobials [ 8 , 46 , 54 ].…”
Section: Resultsmentioning
confidence: 99%